Rancang Bangun Sistem Informasi Tes Psikologi Kepribadian Untuk Keperluan Pegawai Dengan Metode Edwards Personal Preference Schedule Test (Epps) Dan Intelligence Structure Test (Ist) Pada PT. Menara Teguh Perkasa - Eka Yuni Astuty; Salsadilla Irmalia Eka Putri (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
The personality psychological test is one of the procedures in the selection process for prospective employees in a company. Personality psychology tests are also commonly used as a reference in hiring contract employees to permanent positions and promotions. At PT. Menara Teguh Perkasa (PT. MTP) the test is still carried out manually, namely the use of paper as a medium for psychological tests and the process of filling out the minutes of the implementation of the test which also still uses paper media raises the risk of physical damage. In addition, at the assessment stage, the HRD Staff is required to correct the prospective employee's answers one by one, then convert them into an answer key. This is prone to causing human error so that it will affect the accuracy of the test result report. The purpose of this research is to create a psychological test system to facilitate all processes related to the implementation of tests in companies. This system uses the waterfall development method, the Edwards Personal Preference Schedule (EPPS) method to see how the interests and talents of each prospective employee are as well as the Intelligence Structure Test (IST) method which can describe certain work patterns, measure potential in solving problems, and know how way for prospective employees to adapt to changes in the company environment. Based on the research results, this personality psychological test system can facilitate the process of carrying out personality psychological tests which include inputting prospective employee data and question data by HRD Staff, carrying out tests by Prospective Employees until the test results will be obtained immediately in real time. Then the scoring results of each prospective employee can be seen in the form of reports and graphs by HRD and Division Heads. Keywords: Edwards Personal Preference Schedule, Intelligence Structure Test, Personality Psychology Test